2000
DOI: 10.1002/(sici)1096-9071(200002)60:2<152::aid-jmv8>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of an outbreak of HCV in a hemodialysis unit: Direct sequencing of HCV-HVR1 as an appropriate tool for phylogenetic analysis

Abstract: Infection with hepatitis C virus (HCV) is still a serious problem in hemodialysis patients, despite screening of blood products for anti-HCV antibodies. The prevalence of HCV in HD patients is between 15% and 30% in Germany. We report the molecular epidemiology of an HCV outbreak in a hemodialysis unit in 1997 is determined. HCV hypervariable region 1 (HVR1) was amplified from serum samples of 19 patients by polymerase chain reaction (PCR) and sequenced directly. In addition, HCV isolates from 3 of these 19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The presence of HCV viremia in anti-HCVnegative hemodialysis patients has been frequently reported by others researchers (Bukh et al 1993, Masuko et al 1994, Seelig et al 1994, Pujol et al 1996, Schneeberger et al 1998). Just as in others studies (Caramelo et al 1996, Schroter et al 1997, Fabrizi et al 1999, Grethe et al 2000, we can not exclude recent infections, where the sample was collected during the seronegative window phase, or the existence of impaired immune responses in some of these patients. In addition, 8 of the unconfirmed serological results (1 LIA-negative and 7 LIA-indeterminates) were positive for HCV RNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of HCV viremia in anti-HCVnegative hemodialysis patients has been frequently reported by others researchers (Bukh et al 1993, Masuko et al 1994, Seelig et al 1994, Pujol et al 1996, Schneeberger et al 1998). Just as in others studies (Caramelo et al 1996, Schroter et al 1997, Fabrizi et al 1999, Grethe et al 2000, we can not exclude recent infections, where the sample was collected during the seronegative window phase, or the existence of impaired immune responses in some of these patients. In addition, 8 of the unconfirmed serological results (1 LIA-negative and 7 LIA-indeterminates) were positive for HCV RNA.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest a substantial risk in hemodialysis procedures. Moreover, nosocomial transmission among hemodialysis patients has been reently documented by molecular analysis (Sampietro et al 1995, Grethe et al 2000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the nosocomial transmission of HCV continues to occur (21). Several recent studies provided evidence of patient-to-patient transmission in most of the cases of nosocomial transmission (2, 5, 6, 9, 13, 15-17, 19, 20, 29, 36), although some studies also reported transmission from health care workers to patients and vice versa (10,26,32).In recent years, the use of molecular biology techniques has proven to be a powerful tool in the epidemiological investigation of HCV infection in health care facilities and other settings (2,4,6,9,10,13,15,16,19,20,24,30,32). In particular, phylogenetic tree analysis has often been used to identify the original source of infection.…”
mentioning
confidence: 99%
“…In recent years, the use of molecular biology techniques has proven to be a powerful tool in the epidemiological investigation of HCV infection in health care facilities and other settings (2,4,6,9,10,13,15,16,19,20,24,30,32). In particular, phylogenetic tree analysis has often been used to identify the original source of infection.…”
mentioning
confidence: 99%